2022
DOI: 10.1155/2022/3610038
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Lymphocyte-to-Monocyte Ratio (LMR) in Cancer Patients Undergoing Immune Checkpoint Inhibitors

Abstract: Background. There is accumulating evidence that the lymphocyte-to-monocyte ratio (LMR) is related to the outcomes of cancer patients treated with immune checkpoint inhibitors (ICIs). However, the results remain controversial. Method. Electronic databases were searched to retrieve the studies that explore the relationship between LMR and the efficacy of ICIs. The primary endpoints were overall survival (OS) and progression-free survival (PFS), evaluated by the hazard ratios (HRs) with 95% confidence intervals (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 88 publications
1
5
0
Order By: Relevance
“…Conversely, consistent with the hospital blood monocyte count, increasing monocyte proportion as a total of peripheral blood mononuclear cells (PBMCs) pre-treatment was associated with reduced OS (pre-treatment, P= 0.014, log-rank test), and post-ICB reduced PFS and OS (post-treatment PFS P = 0.028; OS, P= 0.031, log rank test) (Figure 4C). In keeping with previous studies 25 , a higher lymphocyte to monocyte ratio (LMR) at baseline was associated with extended OS (p = 0.035, log-rank) (Supplementary Figure 3).…”
Section: Resultssupporting
confidence: 88%
“…Conversely, consistent with the hospital blood monocyte count, increasing monocyte proportion as a total of peripheral blood mononuclear cells (PBMCs) pre-treatment was associated with reduced OS (pre-treatment, P= 0.014, log-rank test), and post-ICB reduced PFS and OS (post-treatment PFS P = 0.028; OS, P= 0.031, log rank test) (Figure 4C). In keeping with previous studies 25 , a higher lymphocyte to monocyte ratio (LMR) at baseline was associated with extended OS (p = 0.035, log-rank) (Supplementary Figure 3).…”
Section: Resultssupporting
confidence: 88%
“…A survival receiver operating characteristic (ROC) analysis was adopted to identify potential cut-offs that optimally stratify patients into risk groups. Optimal thresholds for blood cell count-derived ratios were determined based on literature reviews [7][8][9][10][11][12][13] and our previous work, where we used those cut-offs and verified their applicability. 14 The cut-off values were set as follows: NLR 3, PLR 160, LMR 2, SII 800 and dNLR 1,9, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 A growing number of studies have illustrated the diagnostic and prognostic values of inflammatory markers, such as LMR, NLR, systemic immune-inflammatory index (SII) and prognostic nutritional index (PNI), in various cancers. [26][27][28][29] Recently, a study found that the Glasgow Prognostic Score (GPS), an inflammation-based prognostic evaluation system comprising measures of C-reactive protein and albumin, showed significant prognostic value in ENKTL. 30 However, the prognostic system is The results showed that the CONUT score was more efficient in predicting ENKTL prognosis than the IPI, KPI and PINK models.…”
Section: Discussionmentioning
confidence: 99%